Approaches and methods in language teaching - Richards, Jack C., 1943-; Rodgers, Theodore S. (Theodore Stephen), 1934-; Cambridge University Press (Cambridge ; New York : Cambridge University Press, 2001)
This second edition is an extensive revision of the first edition of this successful text. Like the first edition, the second edition surveys the major approaches and methods in language teaching, such as grammar translation, audiolingualism, communicative language teaching, and the natural approach. The text examines each approach and method in terms of its theory of language and language learning, goals, syllabus, teaching activities, teacher and learner roles, materials, and classroom techniques. In addition to the approaches and methods covered in the first edition, this edition includes new chapters, such as whole language, multiple intelligences, neurolinguistic programming, competency-based language teaching, cooperative language learning, content-based instruction, task-based language teaching, and The Post-Methods Era. Teachers and teachers-in-training will discover that this second edition is a comprehensive survey and analysis of the major and minor teaching methods used around the world. The book seeks not only to clarify the assumptions behind these methods and their similarities and differences, but also to help teachers explore their own beliefs and practices in language teaching.
-- A brief history of language teaching -- The nature of approaches and methods in language teaching -- The oral approach and situational language teaching -- The audiolingual approach -- Total physical response -- The silent way -- Community language learning -- Suggestopedia -- Whole language -- Multiple intelligences -- Neurolinguistic programming -- The lexical approach -- Competency-based language teaching -- Communicative language teaching.
Includes bibliographical references and indexes.
Keywords: Language and languages -- Study and teaching